2007
DOI: 10.1016/j.febslet.2007.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity and products of side‐reactions catalyzed by jasmonate:amino acid synthetase (JAR1)

Abstract: Jasmonate:amino acid synthetase (JAR1) is involved in the function of jasmonic acid (JA) as a plant hormone. It catalyzes the synthesis of several JA-amido conjugates, the most important of which appears to be JA-Ile. Structurally, JAR1 is a member of the firefly luciferase superfamily that comprises enzymes that adenylate various organic acids. This study analyzed the substrate specificity of recombinant JAR1 and determined whether it catalyzes the synthesis of mono-and dinucleoside polyphosphates, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 37 publications
2
45
0
Order By: Relevance
“…Our structural data show that recruiting less favorable amino acids may interfere with the ability of ATP to bind to FIN219. These results corroborate the results of gas chromatography-mass spectrometry quantification of JA derivatives: In Arabidopsis seedlings, JA-Ile predominates (15,41). Further research is required to identify whether FIN219 has a specific recognition motif for amino acid selectivity.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our structural data show that recruiting less favorable amino acids may interfere with the ability of ATP to bind to FIN219. These results corroborate the results of gas chromatography-mass spectrometry quantification of JA derivatives: In Arabidopsis seedlings, JA-Ile predominates (15,41). Further research is required to identify whether FIN219 has a specific recognition motif for amino acid selectivity.…”
Section: Discussionsupporting
confidence: 84%
“…Overexpression of FIN219 causes a FR-specific hyperphotomorphogenic response. During JA signaling, FIN219 catalyzes the conjugations between JA and various amino acids, such as leucine (JA-Leu), valine (JA-Val), or methionine (JA-Met) (15). The fin219 mutants also have a reduced JA-Ile production and JA response (16).…”
mentioning
confidence: 99%
“…46 Initial work on AtGH3-11 (JAR1) demonstrated that it catalyzes the formation of JA-Ile. 47 Subsequent studies of the Arabidopsis group II AtGH3-2, -3, -4, -5, -6 and -17 show that these enzymes…”
Section: The Gh3 Family: a Common Gene Family In Plantsmentioning
confidence: 99%
“…TCP4-regulated LOX2 catalyzes an early step of JA biosynthesis (Gfeller et al, 2010). Lastly, JASMONATE RESISTANT1 (JAR1) functions in the synthesis of biologically active JA-Ile (Guranowski et al, 2007). All four tested genes (TCP4, LOX2, MYC2, and JAR1) were significantly up-regulated in ago1-27 cotyledons (Fig.…”
mentioning
confidence: 93%